A molecular epidemiology study investigating familial clustering of hepatitis B virus infection in families with unfavorable prognoses in Northwest China. Issue 8 (23rd March 2017) - Yanag, Yuan; Du, Dan; Jin, Li; Tian, Zhen; Li, Qian; Yi, Ruitian; Qiu, Ting; Yang, Daokun; He, Yingli; Liu, Jinfeng; Chen, Tianyan; Zhao, Yingren
Abstract : Hepatitis B virus (HBV) infections and adverse outcome have been demonstrated to show characteristics of familial clustering. The aim of this study was to investigate the prevalence of different HBV genotypes, HBV sub‐genotypes, and Pre‐S mutations associated with familial HBV infection clusters with unfavorable prognoses. Families presenting with clustered HBV infections and unfavorable prognoses were enrolled in this study. Non‐clustered HBV‐infected individuals were used as the control group. DNA extracted from patient serum samples was used to facilitate characterization of the HBV genotypes, HBV sub‐genotypes, and Pre‐S mutations by phylogenetic analysis. The Pre‐S/S gene was successfully amplified in 83 patients from the clustering group and 105 patients from the sporadic group. The prevalence of genotype C in the clustering group (71/83, 85.54%) was significantly higher than in the sporadic group (77/105, 73.33%) ( P = 0.042). The prevalence of sub‐genotype C2 in the clustering group (33/83, 39.76%) was also higher than in the sporadic group (21/105, 20%) ( P = 0.003). Analyses of functional mapping of pre‐S sequences showed that the prevalence of the mutation in the S promoter site (nt 3045‐3189 of pre‐S1 domain) was significantly increased in the clustering group compared with the sporadic group (15.7% vs. 3.8%) ( P = 0.009). This study suggests that genotype C, especially sub‐genotype C2, may be associated with the progression of HBV infection in familial clustering infection cohorts with unfavorable prognoses. We also observed that the natural occurrence of S promoter mutations in the clustering group was significantly prevalent.